Comparing the effects of task-switching and language-switching on working memory in bilingual young adults - Huang, Ruijia (Nanyang Technological University, 2023)
Title: Comparing the effects of task-switching and language-switching on working memory in bilingual young adults Objective: To compare the costs to cognitive resources incurred by domain-general and domain-specific switching Methods: A computer-paced, within-subject experiment was designed. A total of 38 participants aged 18-25 performed complex span tasks, where they needed to memorise 5 serially presented coloured shapes, verbally process 8 digits, and recall the shapes. There were 4 conditions in the processing component: task-switching, language-switching, single-task, and single-language. The duration, pace and number of switches in the processing components were kept constant. Results: Consistent with Hypothesis 1a, absolute recall was significantly lower in the language-switching condition compared to the single-language condition, but contrary to Hypothesis 1b, no significance was found between absolute recall in the task-switching condition and the single-task condition. Support was found for Hypothesis 2 as no significant difference in absolute recall was found between task- and language-switching. But for partial recall, there was no significant difference among all the conditions. Conclusion: Task- and language-switching incurred similar cognitive costs, as measured by WM. In addition, participants likely have superior efficiency in single-language processing, either through binding or practices in inhibition. These findings contribute to the understanding of the nature and burden of linguistic versus non-linguistic switching practices.